Results of a clinical study of the drug efficacy and safety for intravesical administration based on bacteriophages in therapy in patients with chronic recurrent cystitis - Andrei V. Zaitsev; Oksana A. Arefeva; Natalia A. Sazonona; Vladimir D. Melnikov; Yuriy A. Kim; Arseniy A. Shiryaev; Alexander O. Vasilyev; Igor O. Gritskov; Alexander V. Govorov; Dmitry Yu. Pushkar (IP Berlin A.V., 2021)
Background. Urinary tract infections remain one of the urgent problems in the aspect of qualified medical care. The causative agents of nosocomial infections are becoming more and more resistant to the drugs used, while the rate of new drugs synthesis is lower than the rate of development of antibiotic resistance. Routine and empirical prevention of recurrent urinary tract infections is often ineffective. Aim. To study the efficacy and safety of intravesical application of the drug based on bacteriophages in therapy in patients with chronic recurrent cystitis. Materials and methods. A clinical study was carried out to study the efficacy and safety of the drug for intravesical administration based on bacteriophages in therapy in patients with chronic recurrent cystitis. The study included 75 patients who were divided into 3 groups in a 1: 1: 1 ratio. In the main group, the drug for intravesical administration based on bacteriophages, as well as rectal suppositories with bacteriophages were used; in the control group only a drug for intravesical administration based on bacteriophages or rectal suppositories with bacteriophages. On visits 1-4, all patients underwent a clinical blood test, general urine analysis, bacteriological urine analysis, as well as urine analysis by the polymerase chain reaction method. The analysis of the patients condition in groups was carried out according to the dynamics of main clinical symptoms changes, data from validated scales for assessing pelvic pain and urgency/frequency of urination and assessment of symptoms of acute cystitis (Acute Cystitis Symptom Score ACSS), as well as the dynamics of changes in objective parameters of laboratory studies and possible changes in sensitivity uropathogens to antibacterial drugs. Results. The average age of the patients included in the study was 50.6 years. In all 3 groups, bacteriological examination of urine showed a predominant growth of Escherichia coli (3104 CFU/ml). In the course of the study, there was a good tolerance to therapy, a decrease in clinical symptoms, as well as a significant decrease in the total score according to the pelvic pain scale and urgency/frequency of urination and the ACSS scale in all patients. Conclusion. The emergence of a large number of microorganisms resistant to various antibiotics and their rapid spread in the environment has led to an increase in scientific interest in bacteriophage therapy as an alternative method of treatment. The overall subjective effectiveness of the therapy in our study was more than 80%, safety - 100%. Further research will allow for a personalized approach to the treatment of infectious diseases of the urinary system.